Ontogeny of the articulated yiliangellinine trilobite Zhangshania typica from the lower Cambrian (Series 2, Stage 3) of southern China. (28th November 2016) - Hou, Jin-bo; Hughes, Nigel C.; Yang, Jie; Lan, Tian; Zhang, Xi-guang; Dominguez, Chrysalyn
Abstract: New discoveries of the early Cambrian yiliangellinine trilobite Zhangshania typica Li and Zhang in Kunming preserve almost all instars from early postembryonic (protaspid) to mature (holaspid) phases in articulated state, in addition to mature specimens with antennae bearing paired spines on the basal articles. The ontogenetic series shows protarthrous development with some, but likely not all, early holaspid instars expressing additional pygidial segments, gradual rearward migration of the location of the longest pleural spines on the trunk segments, and striking positive allometry of the genal spines. It also reveals Parazhangshania sichuanensis Li and Zhang, 1990 to be the holaspid stage 3 of Z . typica, and therefore its junior synonym. This new find in the Hongjingshao Formation provides species-based regional correlation across the South China block and Z . typica may provide an important biostratigraphic marker for the base of the traditional Tsanglangpuan Stage.